Testing Marx - Charlotte Bartels; Felix Kersting; Nikolaus Wolf (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We study the dynamics of capital accumulation, income inequality, capital concentration, and voting up to 1914. Based on new panel data for Prussian regions, we re-evaluate the famous Revisionism Debate between orthodox Marxists and their critics. We show that changes in capital accumulation led to a rise in the capital share and income inequality, as predicted by orthodox Marxists. But against their predictions, this did neither lead to further capital concentration nor to more votes for the socialists. Instead, trade unions and strike activity limited income inequality and fostered political support for socialism, as argued by the Revisionists.
Keywords: D31; D63; J31; N30; 330; income inequality; concentration; top incomes; capital share; capital accumulation